EFEKTIFITAS DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PRODUK KREATITIF DAN KEWIRAUSAHAAN PESERTA DIDIK KELAS XII. TKJ SMK NEGERI I PEMALANG - KARNOTO KARNOTO (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2021)
This research is a classroom action research. This study aims to improve the learning process and improve learning outcomes for Creative Products and Entrepreneurship by applying the Discovery Learning model. The subjects of this study were students of class XII TKJ 3 SMK Negeri 1 Pemalang in the even semester of the 2020/2021 school year which consisted of 17 male students and 19 female students. In the implementation of the learning process before taking action, there are problems, namely learning is still teacher-centered so that students are not able to find concepts from the material being studied. To overcome these problems, a learning model is needed where students can actively find their own concepts being studied. The data collection instruments in this study were observation sheets and learning outcomes tests for Creative Products and Entrepreneurship. The observation sheets were analyzed descriptively by narrative, while the test of learning outcomes for Creative Products and Entrepreneurship were analyzed descriptively. From the analysis, it can be seen that there was an improvement in the learning process from before the action to cycle I and cycle II and an increase in learning outcomes for Creative Products and Entrepreneurship for class XII TKJ 3 SMK Negeri 1 Pemalang students in the even semester of the 2020/2021 academic year. ABSTRAKPenelitian ini merupakan penelitian tindakan kelas. Penelitian ini bertujuan untuk memperbaiki proses pembelajaran dan meningkatkan hasil belajar Produk Kreatif dan Kewirausahaan dengan menerapkan model Discovery Learning. Subjek penelitian ini adalah Peserta Didikkelas XII TKJ 3 SMK Negeri 1 Pemalang semester genap tahun pelajaran 2020/2021 yang terdiri dari 17 Peserta Didiklaki-laki dan 19 Peserta Didikperempuan. Pada pelaksanaan proses pembelajaran sebelum dilakukan tindakan, terdapat permasalahan yaitu pembelajaran masih berpusat pada guru sehingga Peserta Didiktidak mampu menemukan konsep dari materi yang dipelajari. Untuk mengatasi permasalahan tersebut diperlukan suatu model pembelajaran dimana Peserta Didikdapat secara aktif menemukan sendiri konsep yang dipelajari. Instrumen pengumpulan data dalam penelitian ini adalah lembar pengamatan dan tes hasil belajar Produk Kreatif dan Kewirausahaan. Lembar pengamatan dianalisis secara deskriptif naratif, sedangkan tes hasil belajar Produk Kreatif dan Kewirausahaan dianalisis secara statistik deskriptif. Dari analisis terlihat bahwa terjadi perbaikan proses pembelajaran dari sebelum tindakan ke siklus I dan siklus II dan peningkatkan hasil belajar Produk Kreatif dan Kewirausahaan Peserta Didikkelas XII TKJ 3 SMK Negeri 1 Pemalang pada semester genap tahun pelajaran 2020/2021.